VISIBLE INTANGIBLE ASSET EFFICIENCY AND TANGIBLE ASSETS EFFICIENCY: WHO CONTRIBUTES MORE TO THE BUSINESS PERFORMANCE OF AGRICULTURAL FIRMS? - Ognjanović, Jasmina; Pantić, Nemanja; Podovac, Milena (Economics of Agriculture, 2024)
The realization of business activities is carried out by agricultural firms using available assets. Assets can be tangible and intangible. Theoretical and practical experiences show that these two types of assets affect firm value, create a competitive advantage, are a significant driver of productivity growth, and a key factor for the firm’s survival in crisis. The paper aims to analyze the contribution of visible intangible assets efficiency and tangible assets efficiency to the business performance of agricultural firms, monitored through labor productivity, profitability, and firm growth. The sample consists of 42 agricultural firms that operated in 2023 in Serbia. A regression model was used to test the hypotheses. The results prove the contribution of visible intangible assets efficiency and tangible assets efficiency to the productivity of agricultural firms. At the same time, the influence of these variables on firm growth and profitability was absent.